2022
DOI: 10.1038/s41398-022-01832-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs serve as prediction and treatment-response biomarkers of attention-deficit/hyperactivity disorder and promote the differentiation of neuronal cells by repressing the apoptosis pathway

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a highly heritable neurodevelopmental disorder. This study aimed to examine whether miRNA expression abundance in total white blood cells (WBCs) facilitated the identification of ADHD and reflected its response to treatment. Furthermore, whether miRNA markers facilitated the growth of the human cortical neuronal (HCN-2) cells was also investigated. Total WBC samples were collected from 145 patients and 83 controls, followed by RNA extraction and qPCR assays. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…In our cohort, these environmental influences caused by a parent with depression or criminal convictions could have occurred during embryonic development, early infancy, or adolescence altering the expression of genes associated with ADHD and, in turn, affecting brain function with subsequent changes in behavior. Consistent with this idea, previous research indicated epigenetic modifications linked to ADHD such as DNA methylation, histone modifications and expression of noncoding micro RNAs (miRNA) [44][45][46][47][48][49]. Alternatively, the importance given to both parental criminal convictions and depression could be driven by the co-occurrence of ADHD in the parents rather than these two conditions per se, and thus, indirectly predicting the offspring ADHD due to the high heritability of the disorder.…”
Section: Discussionmentioning
confidence: 87%
“…In our cohort, these environmental influences caused by a parent with depression or criminal convictions could have occurred during embryonic development, early infancy, or adolescence altering the expression of genes associated with ADHD and, in turn, affecting brain function with subsequent changes in behavior. Consistent with this idea, previous research indicated epigenetic modifications linked to ADHD such as DNA methylation, histone modifications and expression of noncoding micro RNAs (miRNA) [44][45][46][47][48][49]. Alternatively, the importance given to both parental criminal convictions and depression could be driven by the co-occurrence of ADHD in the parents rather than these two conditions per se, and thus, indirectly predicting the offspring ADHD due to the high heritability of the disorder.…”
Section: Discussionmentioning
confidence: 87%
“…A number of miRNAs are known to regulate PTEN expression, 25 and prior studies have underscored the utility of miRNA profiles as discerning biomarkers for evaluating treatment efficacy. 26 , 27 , 28 To that end, we analyzed PTEN messenger RNA expression levels in PBMCs before treatment and at 3 and 9 months after treatment initiation. The analysis revealed PTEN upregulation after alpelisib treatment ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs are small non-coding RNAs that typically suppress gene expression. Using the next-generation sequencing (NGS) technique (Illumina) and support vector machine classification model, several microRNAs were identified by different groups with the potential to diagnose ADHD (68)(69)(70)(71)(72), which required to be tested in future clinical studies to identify the optimal combination. A large epigenome-wide association study (EWAS) discovered several novel epigenetic biomarkers for ADHD from saliva DNA samples, for example, cg17478313 annotated to SLC7A8 and cg21609804 annotated to Microtubule Affinity Regulating Kinase (MARK)2 that are regulated by single nucleotide polymorphisms (SNPs) (65).…”
Section: Molecular Biomarkersmentioning
confidence: 99%